2015
DOI: 10.11591/ijaas.v4.i2.pp45-49
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Concrete Reinforced with Polypropylene Fibers

Abstract: This research study the mechanical properties of lightweight concrete reinforced with polypropylene fibers. Foam agent used to produce lightweight foamed concrete. The aim of this study to investigate the effect of polypropylene fibers on mechanical properties of lightweight foamed concrete. The volume fractions of the polypropylene fibers (PPF) used are: 0.0%, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% total volume of concrete. The flowability, dry density, compressive strength and splitting tensile strength, were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Several researchers have shown the efficiency of PP fibers in increasing the tensile strength of foam concrete beams. Hamad (2015) studied the mechanical properties of lightweight concrete reinforced with PP fibers to investigate the effect of PP fibers on mechanical properties of lightweight foam concrete. The author concluded that the workability of lightweight foam concrete reduced by addition PP fibers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several researchers have shown the efficiency of PP fibers in increasing the tensile strength of foam concrete beams. Hamad (2015) studied the mechanical properties of lightweight concrete reinforced with PP fibers to investigate the effect of PP fibers on mechanical properties of lightweight foam concrete. The author concluded that the workability of lightweight foam concrete reduced by addition PP fibers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Graybeal ve Davis [36], ultra yüksek dayanımlı lifli betonlar için küp ve silindir numuneler üretmişler ve elde ettikleri deney sonuçlarını karşılaştırdıklarında, lifli betonların karışım dizaynına bağlı olarak küp ve silindir deneylerinden elde edilen basınç dayanımı dönüşüm katsayılarının değişebileceğini bildirmişlerdir. Hamad [37], cam lif ve hafif agrega katkılı beton numunelerin basınç dayanımlarını karşılaştırdığı farklı boyutlardaki silindir ve küp numunelerden elde ettiği sonuçların numune şekli, boyutu ve lif oranına bağlı olarak değiştiğini belirtmiş ve göz önüne alınan her durum için farklı dönüşüm katsayıları elde etmiştir.…”
Section: Deneysel Veri Tabanıunclassified
“…Generally, improving tensile strength may adversely affect on corresponding elongation. Physical and mechanical properties of polyproplene are listed in Table (2) [34][35][36][37]. It is found that trapping properties of matrix are highly modified by the presence of costless nanofillers clay.…”
Section: Physical and Mechanical Properties Of Polypropylene (Pp)mentioning
confidence: 99%
“…In the field of dielectrics and electrical insulation, polymer nanocomposites are known for their excellent dielectric properties and are the subject of intensive research. For example, polymer-clay nanocomposites are considered promising as electrical insulation for power apparatus, cablesand wires in the near future due to their good insulating capabilities, flame retardance and mechanical properties [34]. Thermoplastic and thermoset resins reinforced by nanoparticles of clay, silica, rutile and alumina have been developed and studied [35].…”
Section: Consequence Of Nanotechnology Science On Dielectrics Propertiesmentioning
confidence: 99%